PEMBUATAN STORYLINE VIDEO DOKUMENTER SEBAGAI UPAYA PELESTARIAN PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE (PSHT) DI KOTA MADIUN - Marsha Asyafa Fanani; Diana Aqidatun Nisa; Bayu Setiawan (Universitas Negeri Makassar, 2024)
Its culture is so vast, thus worthy of preservation for the younger generation to prevent Indonesian culture from easily disappearing. Indonesia is a unified nation that cherishes its culture and traditions. The Brotherhood of Setia Hati Terate (PSHT) is one of the leading schools of Pencak Silat in Indonesia, founded by Ki Ngabehi Surodiwiryo, a renowned martial arts figure who also pioneered the Setia Hati (SH) style of Pencak Silat in the early 19th century. The Brotherhood of Setia Hati Terate (PSHT) is known as the most comprehensive silat institution because it integrates five fundamental aspects: spiritual, self-defense, art, sport, and mental discipline. Designing a documentary video to preserve Pencak Silat within the Brotherhood of Setia Hati Terate (PSHT) in Madiun is a fitting and intriguing endeavor to impart knowledge about Pencak Silat within that context. The methodology employed in this design is both qualitative and quantitative, utilizing various approaches such as interviews, observations, questionnaires, and literature review. The resulting keyword,